(untitled) (Bangladesh Journal of Animal Science, 2016)
The present study was conducted to know the chemical qualities and adulteration of fresh raw milk collected from local markets (Bhangnamari bazaar, Sutiakhali bazaar, Vabokhali bazaar, Shombhuganj bazaar and Mymensingh sadar bazaar) of Mymensingh sadar, Bangladesh. Milk samples were analyzed for chemical parameters (contents of acidity, total solids, solids-not-fat, fat, protein and ash) and adulteration (presence of formalin, sugar or starch). Also, lactometer reading was recorded to monitor the specific gravity of the collected milk samples. Result showed that the specific gravity of milk from different sources differed non-significantly. The total solids, fat and protein contents of all the samples were in normal range except the milk fat content collected from Shombhuganj bazaar (32.66±4.04 g/Kg) and Mymensingh sadar bazaar (30.66±4.51 g/Kg) which had less (p<0.01) than the minimum legal standard of milk fat (35.00 g/Kg). The solids-not-fat content of the milk samples collected from Bhangnamari bazaar (72.93±8.78 g/Kg) and Vabokhali bazaar (79.33±6.81 g/Kg) were less than that from Mymensingh sadar bazaar (95.67±11.72 g/Kg). Developed acidity was detected in the samples from Bhangnamari bazaar (0.180±0.03), Sutiakhali bazaar (0.187±0.04%) and Mymensingh sadar bazaar (0.180±0.02%), while other samples were found to the fresh (0.150-0.157%). All of the adulteration tests showed negative results. The results suggested that though there were some fluctuations in quality among the bazaars regarding the standard of parameters, the raw milk samples were of acceptable quality. Bang. J. Anim. Sci. 2016. 45 (2): 73-78